Odpowiedzi

2009-12-14T21:05:16+01:00
Zadanie 1.
a) 2x-3≤ -(2x+1)+2
2x-3≤ -2x-1+2
4x ≤ 4
x ≤ 1

b) 4(x-1) +1 ≤ 3(2x+1)
4x-4 ≤ 6x+3
2x ≥ -7
x ≥ -3,5

c) 3(2-x) > 2(3+x)
-3x+6 > 2x+6
-5x > 0
x<0

d) 5x-4 < 3(x+2)- 2(x-1)
5x -4 < 3x+6 -2x +2
5x-4 < x+8
4x < 12
x < 3

e) 2(3x+2) -7 ≤ -3(2x-3)
6x+4 -7 ≤ -6x+9
12x ≤ 6
x ≤ ½

f) 6- 3/2x > 4-4/3x
½x > -2
x > -4

Zadanie 2.
a) 7x+5 ≤ 4x+50
3x ≤ 45
x ≤ 15

b) 9x+3 > 8x+6
x > 3

c) 8x > 9x-9
x < 9

d) 9x -15 ≥ 4(2x-5) + 6x
9x -15 ≥ 8x- 20 +6x
9x -15 ≥ 14x- 20
-5x ≥ -5
x ≤ 1
2009-12-14T21:17:51+01:00
1 . a ) 2x - 3 </ - ( 2x +1 ) + 2
2x - 3 </ - 2x - 1 + 2
2 x + 2x </ - 1 + 2 + 3
4x </ 4 / : 4
x </ 1

b) 4 ( x - 1 ) + 1 </ 3 ( 2x + 1 )
4x - 4 + 1 </ 6x + 3
4x - 6x </ 3 +4 - 1
- 2x </ 6 / : - 2
x >/ - #


c ) 3 ( 2- x ) > 2 ( 3 + x )

6 - 3x > 6 + 2x
- 3x - 2x > 6 + 6
- 5x > 12 / : - 5
x < 2 , 4


d ) 5x - 4 < 3 ( x + 2 ) - 2 ( x - 1 )
5x - 4 < 3x + 6 - 2x +2
5x - 3x + 2x < 6 + 2 + 4
4x < 12 / : 4
x < 3

e ) 2 ( 3x + 2 ) - 7 </ -3 ( 2x - 3 )
6x + 4 - 7 </ - 6x + 9
6x + 6x </ 9 - 4 + 7
12 x </ 12 /: 1
x </ 1


2009-12-14T21:18:00+01:00
Zad1
a) 2x-3≤-(2x+1)+2
2x-3≤-2x-2+2
2x-3≤-2x+1
b)4x-3+1≤6x+3
c)6-3x>6+2x
d)5x-4<x+4
e)6x+4-7≤-6x+9
f)6-1½x>4-1⅓x

zad2
a)7x+5÷2/*2≤2x=25
14x+10≤2x+25
b)3x+1:2/*2>4x+3/*3
6x+2>12x+9
c)2/3x-2/9x>x-1:2/*2
6/9x-2/9x>2x-2
d)3x-5:2/*2≥2/3(2x-5)+x
6x-10>4/3x-10/3+x
6x-10>2⅓x-10/3